Montelukast, an Anti-asthmatic Drug, Inhibits Zika Virus Infection by Disrupting Viral Integrity - Chen, Yongkang; Li, Yuan; Wang, Xiaohuan; Zou, Peng (Frontiers in Microbiology, 2020)
The association of Zika virus (ZIKV) infection and severe complications including neurological sequelae especially fetal microcephaly has aroused global attentions since its outbreak in 2015. Currently, there are no vaccines or therapeutic drugs clinically approved for treatments of ZIKV infection, however. And the drugs used for treating ZIKV in pregnant women require a higher safety profile. Here we identified an anti-asthmatic drug, montelukast, which is of safety profile for the pregnant and exhibited antiviral efficacy against ZIKV infection in vitro and in vivo. And we showed that montelukast could disrupt the integrity of the virions to release the viral genomic RNA hence irreversibly inhibited viral infectivity. In consideration of the neuro-protective activity which montelukast possessed previously reported, it is promising that montelukast could be used for patients with ZIKV infection, particularly for the pregnant women.